The Ran Pathway in Drosophila melanogaster Mitosis - Chen, Jack W. C.; Barker, Amy R.; Wakefield, James G. (Frontiers in Cell and Developmental Biology, 2015)
Over the last two decades, the small GTPase Ran has emerged as a central regulator of both mitosis and meiosis, particularly in the generation, maintenance and regulation of the microtubule (MT)-based bipolar spindle. Ran-regulated pathways in mitosis bear many similarities to the well-characterized functions of Ran in nuclear transport and, as with transport, the majority of these mitotic effects are mediated through affecting the physical interaction between karyopherins and Spindle Assembly Factors (SAFs) - a loose term describing proteins or protein complexes involved in spindle assembly through promoting nucleation, stabilization, and/or depolymerization of MTs, through anchoring MTs to specific structures such as centrosomes, chromatin or kinetochores, or through sliding MTs along each other to generate the force required to achieve bipolarity. As such, the Ran-mediated pathway represents a crucial functional module within the wider spindle assembly landscape. Research into mitosis using the model organism Drosophila melanogaster has contributed substantially to our understanding of centrosome and spindle function. However, in comparison to mammalian systems, very little is known about the contribution of Ran-mediated pathways in Drosophila mitosis. This article sets out to summarize our understanding of the roles of the Ran pathway components in Drosophila mitosis, focusing on the syncytial blastoderm embryo, arguing that, far from being superfluous, it can provide important insights into the conserved functions on Ran during spindle formation.